2020
DOI: 10.1088/1748-605x/ab9550
|View full text |Cite|
|
Sign up to set email alerts
|

A dual-phase scaffold produced by rotary jet spinning and electrospinning for tendon tissue engineering

Abstract: Tendon is a highly hierarchical and oriented tissue that provides high mechanical strength. Tendon injuries lead to loss of function, disability, and a decrease in quality of life. The limited healing capacity of tendon tissue leads to scar tissue formation, which can affect mechanical strength and cause a re-tear. Tissue engineering can be the solution to achieving complete and proper healing of tendon. The developed constructs should be mechanically strong while maintaining a suitable environment for cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Histological findings also showed enhanced proliferation of fibroblasts and epithelialization and they were significantly better in RFF group than in silver and free groups. Shukla et al measured the hydroxyproline levels of wound tissues such as biomarker of amount of collagen (cellular repair building materials) [ 36 ]. In this current study, collagen was evaluated by Masson's trichrome stain and fibrosis indicated collagen bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Histological findings also showed enhanced proliferation of fibroblasts and epithelialization and they were significantly better in RFF group than in silver and free groups. Shukla et al measured the hydroxyproline levels of wound tissues such as biomarker of amount of collagen (cellular repair building materials) [ 36 ]. In this current study, collagen was evaluated by Masson's trichrome stain and fibrosis indicated collagen bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research has investigated various strategies for guiding stem cell phenotypic expression and manipulating tendon matrix properties using different fibrous scaffolds ( Guner et al, 2020 ; Sarıkaya and Gümüşderelioğlu, 2021 ; Zhu et al, 2021 ). The stem cells formed more mature tendinous tissue on aligned fibers and displayed greater osteogenic differentiation on random fibers ( Yin et al, 2015a ; Orr et al, 2015 ; Guner et al, 2020 ). The mechanical properties and self-assembly of insoluble collagen fibers are more similar to natural collagen ECM than those of soluble collagen.…”
Section: Nanofiber-based Scaffoldsmentioning
confidence: 99%
“…Fibrous scaffolds produced using various fiber‐based fabricating techniques are recognized to be suitable for replacing anisotropic tissues and to promote their healing. [ 94–99 ] The specific structure enables them to mimic the collagen organization, to guarantee mechanical support and tissue infiltration during the regeneration process. [ 100–103 ] In this article, we have mainly focused on the analysis of the utilization of fiber‐based architectures including strand fibers, woven, knitted, braided, and braid‐twisted fibrous structures as well as electrospun, wet‐spun and multilayered fibrous constructs.…”
Section: Fiber‐based Engineered Scaffolds For Tendons and Ligamentsmentioning
confidence: 99%